Abundance, Population Structure and Feeding Habits of Ghost Shrimp Karumballichirus karumba, (Poore and Griffin 1979) (De-capoda, Callichiridae), from Intertidal Zone of the Madura Strait, Indonesia - Abdul Qadir Jailani; Suradi Wijaya Saputra; Aninditia Sabdaningsih (Journal of Aquaculture and Fish Health, 2026)
Environmental pressures can have a negative impact on fishery resources in the Madura Strait, especially the ghost shrimp K. karumba, which provides ecological benefits. Therefore, this study aims to examine the abundance, population structure, and feeding habits of these species. The study was conducted at two stations, each with three 5 x 5 m transects over one year, measuring carapace length (mm) and weight (g). Additionally, intestinal samples were collected to examine feeding habits. The highest abundance of males and females was in transect 1a and 2b, respectively, with males of 83 ind/5m2, females of 111 ind/5m2, and 91 ind/5m2, 104 ind/5m2. The abundance of ovigerous female/gonad maturity level IV was mostly found in September, November, and December. The minimum carapace length of males ranges from 4.63 mm to 16.9 mm with a body weight between 4.88 g and 11.1 g, while the maximum carapace length ranges from 24.31 mm to 40.9 mm with a body weight between 21.5 g and 44.2 g. Minimum carapace length for females ranges from 7.5 mm to 15.3 mm with a body weight between 5.66 g and 12.4 g, and the maximum carapace length ranges from 21.3 mm to 35.4 mm with a body weight between 16.74 g and 33.9 g. The standard degree of morisita (Ip) states that the distribution of ghost shrimp is classified as a clustered distribution pattern. The primary food source of the ghost shrimp K. karumba is organic matter, and supplementary food is Chlorococcum sp. and Chlorella sp.